Collapse transition in random copolymer solutions - Dasmahapatra, Ashok Kumar; Kumaraswamy, Guruswamy; Nanavati, Hemant (Macromolecules, 2006)
We present dynamic Monte Carlo lattice simulations of the coil to globule collapse of single chains of a copolymer comprising monomer units, m and c, wherein there is a net attractive interaction between c-units. As the copolymer is cooled, the solvent quality becomes poorer, and the size of the chain decreases, driven by the net m-m and c-c attractions. The strong c-c attraction increases the overall solvophobicity of the chain relative to a homopolymer and, therefore, copolymers collapse more abruptly and at a higher effective temperature relative to homopolymers. We compare copolymers with homopolymers by rescaling collapse data to the same theta values to account for the effect of overall solvophobicity. This comparison shows that the behavior of copolymers and the corresponding homopolymers is identical as the chain size reduces from high temperatures to the theta value. Beyond theta, copolymers with c-content < similar to 50% collapse more abruptly than either homopolymer, after accounting for the difference in overall solvophobicity. Collapse of copolymers containing higher c-content is dominated entirely by the c-c attractions, and these chains behave qualitatively like homopolymers with a higher effective solvophobicity. Analysis of the chain structure during collapse provides a structural reason for the qualitative change in copolymer collapse at low c-content. When such copolymers are cooled below theta, the c-units rapidly aggregate to form an isotropic, compact core surrounded by an anisotropic solvated shell of m-units. The shell densifies as the copolymer is further cooled, but remains anisotropic for the finite chain sizes investigated.

Pathway to copolymer collapse in dilute solution: uniform versus random distribution of comonomers - Dasmahapatra, Ashok Kumar; Nanavati, Hemant; Kumaraswamy, Guruswamy (Journal of Chemical Physics, 2007)
Monte Carlo simulations show that copolymers with uniformly (or periodically) distributed sticky comonomers collapse ``cooperatively,'' abruptly forming a compact intermediate comprising a monomer shell surrounding a core of the aggregated comonomers. In comparison, random copolymers collapse through a relatively less-compact intermediate comprising a comonomer core surrounded by a fluffy monomer shell that densifies over a wide temperature range. This difference between the collapse pathways for random and uniform copolymers persists to higher chain lengths, where uniform copolymers tend to form multiple comonomer cores. In this paper, we describe the formation of such an intermediate state, and the subsequent collapse, by recognizing that these arise from the expected balance between comonomer aggregation enthalpy and loop formation entropy dictated by the chain microstructure. (c) 2007 American Institute of Physics.

Polymer crystallization in the presence of ``sticky'' additives - Dasmahapatra, Ashok Kumar; Nanavati, Hemant; Kumaraswamy, Guruswamy (Journal of Chemical Physics, 2009)
The effect of ``sticky'' additives (viz., those that have attractive interactions with the polymer) on polymer crystallization, has been investigated by dynamic Monte Carlo (DMC) simulations. Additive-polymer attractive interactions result in a slowing down of the polymer chain diffusivity in the melt state. Our results show that with increasing additive stickiness, polymer crystallinity decreases monotonically, and thinner crystallites form, viz., crystallization is inhibited by the presence of sticky additives. Unusually, the observed ``specific heat'' peak at the phase transition shows nonmonotonic behavior with additive stickiness, and exhibits a maximum for intermediate values of additive stickiness. While the origins of this unexpected behavior are not clear, we show that it correlates with a large interchange between crystalline and amorphous states of the monomers, in the vicinity of the additives. At this intermediate additive stickiness, we also find that crystallization follows a qualitatively different route-crystallinity shows a non-Avrami-like evolution, unlike the case at low or high additive stickiness.
Keywords: Additives; amorphous state; crystallisation; crystallites; Diffusion; Monte Carlo methods; polymer melts